Resepsi Mualaf Terhadap Konsep Diri Mukmin - Fitriana, Lintang Ayu; Muttaqin, Zaenal (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Institut Agama Islam Negeri (IAIN) Purwokerto, 2020)
This article discusses Muslim converts’ (muallaf) reception on Q.S. al-Mu’minūn (23): 1-11 as a process of self-understanding to become a Muslim and looks for the factors prompting their reception. This article is based on field research on the community of Muslim converts affiliated with the Mualaf Center Solo (MCS). This research employed the theory of Qur’anic reception. The collected data is examined using discourse analysis and then presented descriptively. The research shows that Muslim converts in MSC are capable of comprehending Q.S. al-Mu’minūn (23): 1-11 and of understanding the characters of Muslims described in these verses such as pious, generous, honest, self-discipline, social care, reproduction health awareness, trustworthy, responsible and steady. The Muslim converts, however, have different reception on those verses which was influenced by certain factors, among others are religious motivation, the role of family, social interaction, and self-awareness.